1976
DOI: 10.1113/jphysiol.1976.sp011486
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐sodium antagonism on the frog's heart: a voltage‐clamp study.

Abstract: 6. In Na-free choline-Ringer, a strong contracture developed followed by a spontaneous relaxation. Starting from the relaxed state, application of depolarizing clamps gave rise to phasic contractions with a very slow relaxation while tonic contractions were apparently lacking.7. The results are interpreted in terms of an energy-dependent carrier mechanism exchanging one Ca for two Na ions across the cell membrane. The model implies a strong asymmetry in the rate constants governing the chemical reactions on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

1978
1978
1986
1986

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 44 publications
4
17
0
1
Order By: Relevance
“…Attempts in frog atrium have relied upon examination of ionic currents before and after changes in [Na],, or [Ca]o. Benninger et al (1976) failed to detect any measurable change in current in response to a reduction in [Na]o, but the recent data of Mentrard et al (1984), using a similar experimental procedure, revealed small changes in membrane current that were considered to be consistent with the thermodynamic model of electrogenic Na/Ca exchange proposed by Mullins (1979) . However, any change in the Na/Ca exchange current under these conditions must be quite transient in nature, and would have to be measured quickly, before subsequent changes in [Na] ; could occur (Ellis and Deitmer, 1978).…”
Section: Discussionmentioning
confidence: 93%
“…Attempts in frog atrium have relied upon examination of ionic currents before and after changes in [Na],, or [Ca]o. Benninger et al (1976) failed to detect any measurable change in current in response to a reduction in [Na]o, but the recent data of Mentrard et al (1984), using a similar experimental procedure, revealed small changes in membrane current that were considered to be consistent with the thermodynamic model of electrogenic Na/Ca exchange proposed by Mullins (1979) . However, any change in the Na/Ca exchange current under these conditions must be quite transient in nature, and would have to be measured quickly, before subsequent changes in [Na] ; could occur (Ellis and Deitmer, 1978).…”
Section: Discussionmentioning
confidence: 93%
“…Rink (1977) found no evidence that the Na+-Ca2+ exchange in adrenal medulla could be reversed to give Ca2+ influx. Furthermore, the available evidence shows that Na+-Ca2+ exchange is insensitive to inhibition by C02+ and Mn24 (Rink, 1977; Benninger, Einwlichter, Haas & Kern, 1976). Therefore, even if Ca2+ uptake does occur via a reversal of Na+-Ca+2 exchange we should be able to distinguish it from voltage-dependent Ca2+fluxwhichisinhibitedbylow concentrations of C02+ and Mn2+.…”
Section: Resultsmentioning
confidence: 99%
“…An exchange mechanism between Na and Ca has been observed in other cells, most notably, muscle, nerve, and endocrine. For example, in those cells lowering extracellular Na concentration raises cytoplasmic Ca which then triggers contraction, excitation, and secretion (Brading, 1978;Aguirre, Pinto & Trifaro, 1977;Blaustein, 1974Blaustein, , 1977Ma & Bose, 1977;Baker, 1972Baker, , 1976Baker & McNaughton, 1976;Benninger, Einwachter, Hass & Kern, 1976;Cochrane & Douglas, 1976;Lestowecka & Trifaro, 1974;Reuter, Blaustein & Haeusler, 1973;Reuter & Seitz, 1968). Conversely, in the juxtaglomerular cells lowering extracellular Na raises cytoplasmic concentration of Ca which then inhibits release of renin.…”
Section: Discussionmentioning
confidence: 99%